2023
DOI: 10.1371/journal.pone.0284049
|View full text |Cite
|
Sign up to set email alerts
|

Receiving antenatal care components and associated factors in Northwestern Tanzania

Abstract: Introduction Tanzania had an estimated 5.400 maternal deaths in 2020. Suboptimal quality of antenatal care (ANC) presents a major challenge. It is not known what precisely the uptake of the various ANC components is, such as counseling on birth preparedness and complication readiness, preventive measures and screening tests. We assessed the level of receiving the various ANC components and associated factors in order to identify opportunities to improve ANC. Methods A cross-sectional household survey using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In Tanzania, the maternal mortality ratio is estimated at 104 deaths per 100,000 live births (4). The slow reduction of maternal mortality in Tanzania continues to threaten the achievement of the global agendas of reducing maternal mortality to 70 deaths per 100,000 live births by 2030 as per Sustainable Development Goal 3.1(5) (6). Inadequate uptake of the ANC services and variation around low and middle income countries has led to stagnation in reduction of maternal mortality rate in various areas of the country and pregnancy related complications such as preeclampsia and GDM also resulting into poor childbirth outcomes(1,7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, the maternal mortality ratio is estimated at 104 deaths per 100,000 live births (4). The slow reduction of maternal mortality in Tanzania continues to threaten the achievement of the global agendas of reducing maternal mortality to 70 deaths per 100,000 live births by 2030 as per Sustainable Development Goal 3.1(5) (6). Inadequate uptake of the ANC services and variation around low and middle income countries has led to stagnation in reduction of maternal mortality rate in various areas of the country and pregnancy related complications such as preeclampsia and GDM also resulting into poor childbirth outcomes(1,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of women with overall adequate ANC ranged from 9.6% in Uganda (10), 11% and 19.6% in Ethiopia (11,12) to 21% in Bangladesh (14). Studies from Tanzania, Kenya, and Rwanda have revealed inadequate counseling during ANC, with just 68% of women receiving advice on birth preparedness, 55% on risk indications, 41% on family planning after childbirth, and 17% on nutrition (6). In Tanzania inadequate ANC was reported in a rural district in eastern-central, where hemoglobin was measured in 22 % to 37 % of women and Blood pressure measurement was most common service provided to about 69% and 87% of women attending ANC (14)(15)(16)(17) with the lowest coverage being urine sample taken (18,19).…”
Section: Introductionmentioning
confidence: 99%